Activating CD137 Signaling Promotes Sprouting Angiogenesis via Increased VEGFA Secretion and the VEGFR2/Akt/eNOS Pathway - Bo Li; Yue Zhang; Runting Yin; Wei Zhong; Rui Chen; Jinchuan Yan (Mediators of Inflammation)
Combination of antiangiogenesis and immunotherapy may be an effective strategy for treatment of solid tumors. Our previous work reported that activation of CD137 signaling promotes intraplaque angiogenesis. A number of studies have demonstrated that vascular endothelial growth factor receptor 2 (VEGFR2) is a key target for angiogenesis. However, it is unknown whether CD137-mediated angiogenesis is related to VEGFR2. In this study, we investigated the effect of CD137 on the VEGFR2 expression and explored the underlying mechanisms of CD137-mediated angiogenesis. Knock-out of CD137 in ApoE-/- mice significantly decreased neovessel density in atherosclerotic plaques. CD137 silencing or inhibition attenuated endothelial cell (ECs) proliferation, migration, and tube formation. We found activation of CD137 signaling for increased VEGFR2 transcription and translation steadily. Moreover, CD137 signaling activated phosphorylated VEGFR2 (Tyr1175) and the downstream Akt/eNOS pathway, whereas neutralizing CD137 signaling weakened the activation of VEGFR2 and the downstream Akt/eNOS pathway. The aortic ring assay further demonstrated that CD137 signaling promoted ECc sprouting. Inhibition of VEGFR2 by siRNA or XL184 (cabozantinib) and inhibition of downstream signaling by LY294002 (inhibits AKT activation) and L-NAME (eNOS inhibitor) remarkably abolished proangiogenic effects of CD137 signaling both in vitro and ex vivo. In addition, the condition medium from CD137-activated ECs and vascular endothelial growth factor A (VEGFA) had similar effects on ECs that expressed high VEGFR2. Additionally, activating CD137 signaling promoted endothelial secretion of VEGFA, while blocking CD137 signaling attenuated VEGFA secretion. In conclusion, activation of CD137 signaling promoted sprouting angiogenesis by increased VEGFA secretion and the VEGFR2/Akt/eNOS pathway. These findings provide a basis for stabilizing intraplaque angiogenesis through VEGFR2 intervatioin, as well as cancer treatment via combination of CD137 agonists and specific VEGFR2 inhibitors.